A novel integrated fuzzy PIPRECIA – interval rough SAW model: green supplier selection - Đalić, Irena; Stević, Željko; Karamasa, Caglar; Puška, Adis (Decision Making: Applications in Management and Engineering, 2020)
In this paper is presented a novel integrated fuzzy – rough Multi-Criteria Decision-Making (MCDM) model based on integration fuzzy and interval rough set theory. Model integrates Fuzzy PIvot Pairwise RElative Criteria Importance Assessment - fuzzy PIPRECIA and Interval rough Simple Additive Weighting (SAW) methods. An illustrative example for demonstration of the model is proposed that represents evaluation and supplier selection based on nine environmental criteria. Fuzzy PIPRECIA method is used for determining the significance of the following seven criteria: C1 - environmental image, C2 - recycling, C3 - pollution control, C4 - environmental management system, C5 – environmentally friendly products, C6 - resource consumption and C7 - green competencies. Iterval rough SAW method is applied for evaluation four alternatives. Results show that third criterion is most important while fourth alternative represents the best solution.